The Application Of Khiyar In The Buying And Selling Of Smoked Fish - Hariyani Listiawati; Mursyid; Muh. Adibtiya (DPPM Universitas Pelita Bangsa, 2026)
Khiyar is a choice that must be made when continuing or canceling a sale and purchase transaction contract. The buying and selling process requires khiyar, and the rights of khiyar are stipulated in Islamic law to avoid disputes between buyers and sellers, so that no one is deceived or harmed in buying and selling transactions. The aim of this research is to see how khiyar is applied in the buying and selling activity of smoked fish with a case study at the Mandonga wet market, Lasandara Street, Kendari City. This research uses a qualitative research method with a data analysis approach, namely descriptive qualitative. The theoretical basis used in this research is the application of khiyar Majlis, khiyar 'Aib, and khiyar Terms at the Mandonga wet market, Lasandara Street, Kendari city which is carried out in the activity of buying and selling smoked fish. The informants in this research were 16 people consisting of 6 smoked fish sellers and 10 buyers. This research was carried out using data collection techniques in the form of observation, interviews and documentation. The results of this research show that the application of khiyar, including khiyar Majlis, khiyar 'Aib, and khiyar conditions in buying and selling smoked fish transactions carried out by sellers at the Mandonga wet market, has been successfully implemented based on an Islamic economic review.